VI. The Impact of Intermediate Goods Import on the Improvement of Enterprise Innovation Ability Among One Belt One Road Countries - Liu, Shiying; Wang, Weizhuo (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
This chapter reviews prior research relevant to the import of intermediate goods, firm innovation, and the relationship between the two. Studies on intermediate goods imports focus on their impact on enterprise productivity, global value chain positioning, and export quality. Research on firm innovation explores various influencing factors, including cross-border mergers and acquisitions, imports of intermediate goods, and digital transformation strategies. The literature linking intermediate goods imports and innovation emphasizes the role of technological spillovers, diversification, and quality improvements. Drawing from these insights, this chapter summarizes key findings and offers policy recommendations aimed at enhancing both the quality and volume of China’s intermediate goods imports and strengthening firms’ innovation capabilities.